Implementasi Program Konseling Puspaga Balai RW terhadap Orang Tua Anak Berkebutuhan Khusus - Binti Azizatun Nafi’ah; Berliana Putri, Prizalia (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research examines in depth the implementation of the Family Learning Center (PUSPAGA), focusing on special psychological counseling services for children with special needs (ABK). The main problem raised was the high number of parents who experienced difficulties in responding to their children's special needs, especially related to financial constraints in undergoing therapy and carrying out ABK diagnostic tests. The research method involved data analysis from PUSPAGA services and in-depth interviews with parents who received these services. The research conclusion emphasizes the government's full support in providing welfare services for families with crew members, and highlights the need to expand and increase resources to meet the growing needs in these communities